ChemInform Abstract: Pd‐Catalyzed Stereospecific Allyl—Aryl Coupling of Allylic Alcohols with Arylboronic Acids. Issue 7 (18th February 2014) - Ye, Jiang; Zhao, Jingming; Xu, Jing; Mao, Yuxue; Zhang, Yong Jian
Abstract The coupling reaction of enantiopure allylic alcohols (I) with arylboronic acids (II) and (IV) affords corresponding coupling products as single regioisomers (III) and (V), respectively.